DISTRIBUSI BULU BABI (Echinoidea) DI PERAIRAN PANTAI KAMPUNG BARU BANDA NAIRA, MALUKU - Budiono Senen (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STP Hatta-Sjahrir, 2016)
Distribution Pattern of Sea Urchin in Territorial Water Kampung Baru, Banda Naira. Problems which can result the degradation species that is with consuming continually. Aims of this research that is to see the Distribution Pattern. This research used Transec method, of there are. Apart among/between station 150 m. In each station made by 5 line transec with the distance of every transec 30m. Every mark with lines of some fairish blaze 1 x 1 m, started from highest tide withdraw the low with the distance of each check 10 m. Based calculation, pattern of distribution of Sea urchin look generally species of Sea urchin of at researchlocation of a lot of found by pattern of group distribution of in comparing with density and make an index to Manner.